2016
DOI: 10.1037/per0000127
|View full text |Cite
|
Sign up to set email alerts
|

Self–other disturbance in borderline personality disorder: Neural, self-report, and performance-based evidence.

Abstract: Individuals with borderline personality disorder (BPD) display an impoverished sense of self and representations of self and others that shift between positive and negative poles. However, little research has investigated the nature of representational disturbance in BPD. The present study takes a multi-modal approach. A card sort task was employed to investigate complexity, integration and valence of self-representation in BPD. Impairment in maintenance of self and other representations was assessed using a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 67 publications
(99 reference statements)
6
69
0
Order By: Relevance
“…Thus, BPD patients appear to be able to perceive and differentiate self- versus other-relevant information like healthy controls at an automatic processing level. Our data suggest that there exist no abnormalities in the automatic differentiation between self- and other-related information during the perception of affective words in BPD, even though research using self-report and interviewing techniques has observed abnormalities in representations of the self and others in patients with BPD [19,26] and a lack of differentiated and integrated representations of the self and others [27]. …”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Thus, BPD patients appear to be able to perceive and differentiate self- versus other-relevant information like healthy controls at an automatic processing level. Our data suggest that there exist no abnormalities in the automatic differentiation between self- and other-related information during the perception of affective words in BPD, even though research using self-report and interviewing techniques has observed abnormalities in representations of the self and others in patients with BPD [19,26] and a lack of differentiated and integrated representations of the self and others [27]. …”
Section: Discussionmentioning
confidence: 92%
“…There is evidence that as childhood experiences of punishment increase, the ability in adulthood to accurately identify affect in others and understand social situations deteriorates [25]. Findings from previous research using self-report and interviewing techniques have found empirical evidence for abnormalities in the representations of the self and others in patients with BPD [19,26]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These difficulties comprise one of the symptom criteria, found in section II of DSM-5: "Identity disturbance: markedly and persistently unstable self-image or sense of self [12]." To test the neural correlates of this clinical phenomenon, Beeney and colleagues [78] conducted a study examining self-report measures of self-representation with an fMRI task designed to tap into self-and other-reflection. In the task, participants were 1) asked to evaluate themselves on a certain trait, 2) asked how a close friend would evaluate them on that trait, and 3) asked how that close friend would evaluate themselves on the trait.…”
Section: Neural Network Tom and Bpdmentioning
confidence: 99%